Pengaruh Kualitas Produk, Harga dan E-WOM pada Keputusan Pembelian Konsumen pasca Pandemi Covid-19 dengan Kepercayaan sebagai Variabel Mediasi - Rahmat Fajri Ramadhan; Alfitman; Eri Besra (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to see the effectproduct quality, price and e-wom on consumer purchasing decisions after the Covid-19 pandemic with trust as a mediating variable for Solo meatball consumers in the city of Padang. The population is all consumers of Solo meatballs in the city of Padang. Sampling by purposive sampling method.The sample criteria is that the respondent has visited, bought and eaten at least once at Bakso Solo stalls in Padang City. The number of samples in the study was 270 respondents. Test the hypothesis using statistical analysis using Smart PLS.3.3. The results of the study show that product quality, price and e-WOM have a positive and significant effect on purchasing decisions. product quality, price and e-wom have a significant positive effect on trust. Trust influences purchasing decisions. And trust can be a mediating variable between product quality, price and e-WOM on purchasing decisions in a significantly positive way.